Curcumin attenuates harmful effects of arsenic on neural stem/progenitor cells - Ali Jahanbazi Jahan-Abad; Parastoo Morteza-zadeh; Sajad Sahab Negah; Ali Gorji (Mashhad University of Medical Sciences, 2017)
Objective: Arsenic, an environmental pollutant, decreases neuronal migration as well as cellular maturation and inhibits the proliferation of neural progenitor cells. Curcumin has been described as an antioxidant and neuroprotective agent with strong therapeutic potential in some neurological disorders. Human adipose-derived stem cells (hADSCs), a source of multipotent stem cells, can self-renew and differentiate into neural cells. The aim of the present study was to investigate the preventive effect of curcumin against arsenic toxic effects on the viability, telomerase activity, and apoptosis of neural stem/progenitor cells (NSPCs) derived from hADSCs. Materials and Methods: The characteristics of human adipose tissue were identified by immunocytochemistry for surface markers namely, CD105, CD73, and CD90. Using neurosphere assay, hADSCs were differentiated into neuronal cells. To characterize neural cells, expression of nestin, SOX2, MAP2, and GFAP were assessed by immunocytochemistry. Cytotoxicity and viability of NSPCs were evaluated by MTT assay. Reactive oxygen species (ROS) generated by arsenic exposure, were measured and caspase 3/7 activity and caspase-3 processing as well as the telomerase activity were determined. Results: The isolated hADSCs positively expressed CD105, CD73, and CD90. Nestin, Sox2, GFAP, and MAP2 were expressed in the neurospheres derived from hADSCs. Curcumin/arsenic co-treatment significantly increased telomerase activity of NSPCs compared to arsenic group. Furthermore, curcumin significantly reduced arsenic-induced apoptosis (via inactivation of caspases) as well as arsenic-associated ROS generation. Conclusion: Our findings revealed that curcumin has the potential to prevent harmful effects of arsenic on neurogenesis.